Rancang Bangun Sistem Pemantauan Dosis Radiasi Sinar Gamma di Bawah Permukaan Air Menggunakan Pencacah Geiger-Muller Secara Nirkabel Berbasis Labview - Adhitya Firmansyah; Meqorry Yusfi; Mohamad Nur Yahya (Jurnal Fisika Unand, 2024)
Utilization of various radioactive sources in Indonesia, including nuclear fuel, nuclear waste, and radioactive minerals, has significantly increased to support research, industry, and healthcare services. This usage necessitates an evaluation of environmental impacts, particularly the increase in background radiation in the context of radioecology. Radionuclides like cesium, which are highly soluble in water, can be released into marine waters through leaks from nuclear power plants, radioactive waste, and military weapons tests, potentially harming marine ecosystems and the food chain. Therefore, periodic monitoring of underwater radiation exposure is crucial. This study aims to develop a gamma-ray radiation dose monitoring system underwater using a wireless Geiger-muller counter and LabVIEW-based interface. The system comprises a Geiger-muller counter for measuring radiation doses, an nRF24l01+ module for data transmission, and a LabVIEW application as the display panel. Testing was conducted by submerging a radioactive cesium source into a water tank with varying distances and depths. Radiation data were measured by the Geiger-muller counter, transmitted via the nRF24l01+ to the receiver, processed by Arduino Uno, and displayed in LabVIEW. The LabVIEW application also provides alerts if the dose exceeds the threshold and records the dose values. Test results showed the lowest measurement success rate of 17% at position 7 and the highest of 30% at position 1.